Successful Management of Intraoperatively Diagnosed Ruptured Spontaneous Sub-Capsular Liver Hematoma in a Woman with Preeclampsia - Tegene D; Regassa G; Usu A; Ayalew N (Dove Medical Press, 2021)
Dereje Tegene, Getahun Regassa, Aman Usu, Netsanet Ayalew Department of Obstetrics and Gynecology, Adama Hospital Medical College, Adama, EthiopiaCorrespondence: Dereje TegeneDepartment of Obstetrics and Gynecology, Adama Hospital Medical College, Adama, EthiopiaTel +251913909665Email fekadutd79@gmail.comBackground: Ruptured subcapsular hematoma of the liver is one of the rare life-threatening complications of pregnancy and its incidence varies between 1/45,000 and 1/225,000 births.Case Presentation: A 32-year-old woman who claimed 9 months amenorrhea, presented to our hospital with elevated blood pressure and pushing down pain. After evaluation she was admitted to the labor ward with a diagnosis of latent first stage of labor and preeclampsia with severe features. She gave birth by outlet vacuum. Immediately following delivery she developed hypotension with signs of intra-abdominal fluid collection. Surgical exploration revealed massive hemoperitoneum with ruptured subcapsular hepatic hematoma. She was managed conservatively with pressure packing and drainage tube. The patient improved and was discharged after 12 days of hospital stay.Conclusion: Timely surgical intervention, multidisciplinary team, on-time availability of blood products, and proper postoperative follow up are crucial to optimize the patient outcome.Keywords: Adama, Ethiopia, preeclampsia, ruptured subcapsular liver hematoma